Discourse Analysis In Online Newspapers Regarding The Potential Differences In Ramadan - Arini Vika Sari; Sofyan Pariyasto; Mhd. Abrar Arief (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Study This aiming for analyze news about difference date the beginning of Ramadan between the Minister of Religion and Muhammadiyah in the letter online news. Types of research This is study qualitative, with approach specifically using analysis models discourse critical Teun A. Van Dijk. Analysis method This covers stage identification, description, and interpretation to structure text news. Data sources used is article online news from CNN Indonesia March 6, 2024 entitled Potential Difference in Ramadan Start Date, Minister of Religion and Muhammadiyah Speak Up. Data collection techniques used is technique read and take notes. While technique data analysis used covering data reduction, data presentation, and extraction conclusion. Dimension text Van Dijk's approach is differentiated become three, namely structure macro, suprastructure, and structure micro. Structure macro referring to the meaning the whole thing that can under scrutiny from news. Suprastructure pointing to the frame a news, such as introduction to be continued with Contents main, conclusion, and closing. Whereas structure micro referring to the meaning local a news that can dug up from aspect semantics, syntax, and rhetoric. The results of the study This show that the media is more tend prioritize the authority of the Minister of Religion in determine date the beginning of Ramadan, and emphasized the agreement national. From the results analysis can concluded that information provided has fulfil criteria structure Teun A. Van Dijk model text. Analysis discourse critical disclose existence use language that tends to own objective certain with the party considered more Correct or wrong in determine date the beginning of Ramadan.